Human resource management – sustainable practices - PARZHANOVA, Aneliya (Edelweiss Applied Science and Technology, 2025)
In the modern knowledge economy, the human factor plays a key role in successful business development. At the same time, the turmoil in the global economy and the state of the planet make the idea of sustainable development increasingly prominent. In these conditions, the human factor plays a key role in the successful development of business. The current dynamic business environment requires new techniques for achieving competitive advantage. Human resources, one of the organizations' most valuable assets, must be managed to provide long-term economic benefits and increase employee satisfaction and engagement. Neglecting the human factor in the constant changes of the environment can lead to negative consequences for organizations, which requires sustainable human resource management (HRM) to become part of their overall management framework. The purpose of this article is to review the sustainable management of organizations and the role of the human factor, by presenting a specific combination of people management practices that contribute to improving sustainability, leading to improved long-term development of companies.Views on the significance and essence of sustainable human resource management are summarized.